The availability of emotional intelligence among secondary school managers in Lattakia (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to identify the level of emotional intelligence among secondary school's directors in Lattakia, and study the differences between them at this level depending on variables: sex, academic qualification, and years of experience. This research adopted the descriptive and analytical approach. The research community included all secondary school's directors in Lattakia, totaling 167directors. due to the small size of the research community The research sample consisted Statistical original community after an exclusion (10) directors, Exploratory study was done and therefore Questionnaire was distributed to (157) school's directors, and (146) complete and valid questionnaire for statistical analysis Return in response rate 92.99%. One of the most important results that have been reached: * The level of emotional intelligence among secondary school's directors is high, and the relative importance Reached (72.74%). * The level of the director's emotional intelligence is not affected of sex and place of residence, where it was found a lack of statistically significant differences between mean scores of secondary school's directors in Lattakia in the level of emotional intelligence is due to the variables of sex and place of residence. * The level of the director's emotional intelligence is influenced by his scientific qualification and his years of experience in management, where there are significant differences between the mean scores of secondary school's directors in Lattakia, it was found in the level of emotional intelligence due to the educational qualification variables (graduate and leave college and years of experience), (more than 15 years, 10-15 years).